Peran Pola Pendidikan Taruna Terhadap Kedisiplinan Mahasiswa pada Sekolah Akademi Penerbang Indonesia - Arya Raka Kusuma (Pusat Riset dan Inovasi Nasional, 2024)
Pilot is a skill that a person have to control and operate an aircraft. A person can be said to be someone who is an expert in controlling and operating an aircraft if that person already has a license issued by an authorized institution and has passed a feasibility test. Basically, becoming a pilot is not easy, pilot required to have high level of discipline, intelligence and responsibility. This research have purpose to analyze the influence of cadet education system on the discipline of pilot cadidates at Indonesia Pilot Academy. The results of this research show that the cadet education system influences the discipline of pilot candidates at Indonesia Pilot Academy. Cadet education influences discipline in all aspects of the lives of pilot students at Indonesia Pilot Academy.